Management of patent ductus arteriosus – Evidence to practice - Samir Gupta (584529) (2024)
Over the past last 50 years, patent ductus arteriosus (PDA) continues to be the leading hot topic debated worldwide in search of best treatment approach and the uncertainty around whether to treat or not treat a PDA. With the availability of bedside echocardiography and the increasing number of neonatologists acquiring this skill, on one hand there is better understanding of PDA physiology during transitional circulation and objectivity in management, but on the other hand clinicians are uncertain about benefits in health outcomes. Evidence from recent trials utilizing early selective treatment guided by bedside echocardiography should help in dispelling some myths if not providing the answer about how to manage the PDA. Other Information Published in: Seminars in Fetal and Neonatal Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.siny.2024.101565